Realization of Hollow-Core Photonic-Crystal Fiber Optic Gyro Based on Low-Noise Multi-Frequency Lasers with Intermediate-Frequency Difference - Hongchen Jiao (Sensors, 2020)
Mainly focusing on the demand for a novel resonator optic gyro based on a hollow-core photonic-crystal fiber (HC-RFOG), we achieve a multi-frequency lasers generation with low relative phase noise via an acousto-optic modulation of light from a single laser diode. We design a homologous heterodyne digital optical phase-locked loop (HHD-OPLL), based on which we realize the low-noise multi-frequency lasers (LNMFLs) with an intermediate frequency difference. The noise between the lasers with a 20 MHz difference is 0.036 Hz, within the bandwidth of 10 Hz, in a tuning range of 120 kHz, approximately 40 dB lower than that produced without the HHD-OPLL. Finally, based on the LNMFLs, an HC-RFOG is realized and a bias stability of 5.8 °/h is successfully demonstrated.